Sucrose Exposure in Early Life Alters Adult Motivation and Weight Gain - Frazier, Cristianne R. M.; Mason, Peggy; Zhuang, Xiaoxi; Beeler, Jeff A. (PloS one, 2008)
The cause of the current increase in obesity in westernized nations is poorly understood but is frequently attributed to a 'thrifty genotype,' an evolutionary predisposition to store calories in times of plenty to protect against future scarcity. In modern, industrialized environments that provide a ready, uninterrupted supply of energy-rich foods at low cost, this genetic predisposition is hypothesized to lead to obesity. Children are also exposed to this 'obesogenic' environment; however, whether such early dietary experience has developmental effects and contributes to adult vulnerability to obesity is unknown. Using mice, we tested the hypothesis that dietary experience during childhood and adolescence affects adult obesity risk. We gave mice unlimited or no access to sucrose for a short period post-weaning and measured sucrose-seeking, food consumption, and weight gain in adulthood. Unlimited access to sucrose early in life reduced sucrose-seeking when work was required to obtain it. When high-sugar/high-fat dietary options were made freely-available, however, the sucrose-exposed mice gained more weight than mice without early sucrose exposure. These results suggest that early, unlimited exposure to sucrose reduces motivation to acquire sucrose but promotes weight gain in adulthood when the cost of acquiring palatable, energy dense foods is low. This study demonstrates that early post-weaning experience can modify the expression of a 'thrifty genotype' and alter an adult animal's response to its environment, a finding consistent with evidence of pre- and peri-natal programming of adult obesity risk by maternal nutritional status. Our findings suggest the window for developmental effects of diet may extend into childhood, an observation with potentially important implications for both research and public policy in addressing the rising incidence of obesity.